Comparison of the effect of aerobic and resistance training on fatigue, quality of life and biochemical factors in hemodialysis patients - Naimeh Nakoui; Saeed Ilbeigi; Mohsen Mohammadnia Ahmadi; Azadeh Saber (Scientific Reports)
Abstract Although hemodialysis has been able to increase the lifespan of dialysis patients, it has also brought many problems such as fatigue, low QOL, hypertension and physical weakness to them. Therefore, the aim of this study was to compare the effect of aerobic and resistance training on fatigue, quality of life (QOL), blood Na+, hemoglobin, C-reactive protein (CRP) and urea-creatinine ratio in hemodialysis patients. This research was conducted on 51 patients in two dialysis centers in Kerman, Iran. Patients were randomly divided into resistance group (RG) (n = 17), aerobic group (AG) (n = 17) and control group (CG) (n = 17). The patients in RG and AG performed the training protocol for eight weeks. Research variables as fatigue, QOL, blood Na+, hemoglobin, CRP, and urea-creatinine ratio were measured in pre-test and post-test. Data analysis was done using one-way ANOVA and Tukey’s post hoc tests in SPSS25. (p < 0.05). The mean level of fatigue in RG and AG was significantly lower than the CG (p = 0.001). The mean levels of blood Na+ in AG was significantly higher than RG and CG (p = 0.01). Also, the mean ratio of urea-creatinine in RG and AG were significantly lower than CG (p = 0.001). There was no significant difference in QOL, hemoglobin and CRP between the RG and AG compared to the CG (p > 0.05). Based on our evidence, resistance and aerobic training for 8 weeks, 3 times weekly, is likely to improve the conditions of hemodialysis patients, and might be an option to increase intradialytic exercise adherence. Future studies should determine whether the findings are generalizable and examine the long-term effects of intradialytic exercise training.